UPAYA TEUNGKU DAYAH DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR`AN SANTRI BARU DAYAH IHDAL ULUM AL-AZIZIYAH - Musrizal Musrizal; Musafirul Hadi; Dea Anita (AL-ILMU, 2023)
Dayah is a non-formal educational institution that focuses on educating children. Therefore, dayah is very important for a child, especially in terms of reading the Qur'an. Dayah Ihdal Ulum Al-Aziziyah also focuses on learning the Qur'an. Al-Qur'an learning becomes the main learning even the teachers in the dayah also teach the reading of the Qur'an to the students in particular. However, in reality there are still some students in the Ihdal Ulum Al-Aziziyah Dayah who do not understand about reading the Qur'an both in terms of recitation, makharijul letters and so on. Key Words : Teungku Dayah, Read Al-Qur’an, Santri